Rheological properties of nanocrystalline cellulose suspensions. (10th February 2017) - Chen, Yang; Xu, Chunjiang; Huang, Jing; Wu, Defeng; Lv, Qiaolian
Highlights: NCCs are flocculated and have lower percolation threshold in PVA solution. NCCs have stronger electrostatic repulsion with CMC chain in CMC solution. NCC suspension has weak strain overshoot in PVA solution during LAOS flow. NCC suspension has stronger stress overshoot in CMC solution in startup flow. Two suspensions show strain-scaled stress overshoot behavior in startup flow. Abstract: Rheological behavior, including linear and nonlinear, as well as transient rheology of nanocrystalline cellulose (NCC) suspensions was studied in this work. Two kinds of polymer solutions, aqueous poly(vinyl alcohol) (PVA) with flexible chain structure and aqueous carboxymethyl cellulose (CMC) with semi-rigid chain structure, were used as the suspension media to further explore the role that the interactions among NCC and polymers played during shear flow. The results reveal that NCC has lower values of percolation threshold in the PVA solution than in the CMC one during small amplitude oscillatory shear (SAOS) flow because the flexible PVA chain has higher adsorbed level onto NCC particles than the negatively charged semi-rigid CMC chain, which is further confirmed by the Fourier transformed infrared (FT-IR) spectroscopy tests. As a result, the NCC suspension shows a weak strain overshoot in PVA solution during large amplitude oscillatory shear (LAOS) flow, which cannot be seen on the one in CMC solution. During startup shear flow, both of these two suspensions show evident stress overshoot behavior with the strain-scaling characteristics, indicating the formation of ordered long-term structure of rod-like NCC particles with self-similarity during flow. However, NCC suspension have far stronger stress overshoot response in CMC solution relative to the one in PVA solution. A possible synergy mechanism between NCC and CMC chain is hence proposed.